TPPU Downregulates Oxidative Stress Damage and Induces BDNF Expression in PC-12 Cells. (13th July 2022) - Wu, Qiong; Lin, Minlin; Wu, Peng; Zhao, Chongyan; Yang, Shuang; Yu, Haiying; Xian, Wenjiao; Song, Jingfang
Abstract : Objective . Ischemia-reperfusion is an ongoing clinical challenge that can lead to a series of pathological changes including oxidative stress. The inhibition of soluble epoxide hydrolase inhibitor (sEH) by 1-(1-propanoylpiperidin-4-yl)-3-[4-(trifluoromethoxy)phenyl]urea (TPPU) results in an anti-inflammatory, cardioprotective, and blood vessel growth-promoting effects. Therefore, this study focused on the protective effect of TPPU on a rat pheochromocytoma (PC-12) cell oxidative stress model induced by H2 O2 . Methods . CCK-8 and Hoechst 33342 were used to evaluate cell apoptosis and western blot to detect the apoptotic proteins and brain-derived neurotrophic factor (BDNF) expression. Result . The incubation with 100  μ M, 50  μ M, and 25  μ M TPPU significantly increased PC-12 cell viability. Epoxyeicosatrienoic acid (EET) pretreatment also protected PC-12 cells from oxidative stress. In addition, TPPU reduced caspase-3 and Bax expression and induced Bcl-2 expression, and EETs exerted the same effect on caspase-3 expression as TPPU. A positive relationship was found between TPPU or EET incubation and BDNF expression. Conclusion . These results revealed that TPPU reduced PC-12 cell oxidative stress injury induced by H2 O2 and promoted BDNF expression.